2021
DOI: 10.1038/s41598-021-00077-0
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation and dispersion of Lactobacillus acidophilus in a chocolate coating as a strategy for maintaining cell viability in cereal bars

Abstract: Flour from Pereskia aculeata leaf and green banana were used as ingredients in the formulation of a cereal bar with added Lactobacillus acidophilus LA02-ID-1688. Encapsulation in a calcium-alginate hydrogel reinforced with magnesium hydroxide was used as a strategy to protect the probiotic cells under gastrointestinal conditions and to prolong shelf-life. The results are relevant especially for maintaining cell viability during shelf-life; a challenge for the food industry in relation to dry probiotic products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…In the same study, a positive effect of immobilization was also observed on the maintenance of cell viability during storage (for 180 days), which resulted in higher survival rates of the freeze-dried immobilized cultures on natural carriers (zea flakes and pistachios) in comparison to the free cultures. Regarding storage, low temperatures are known to prolong cell survival and are thus strongly preferred [ 44 , 45 ], but the nature of the carrier should not be neglected, as it may affect the cell viability throughout the final products’ shelf life and survival [ 46 ]. Nevertheless, the possibility of the viability of probiotic cultures (either in free form or immobilized on food ingredients) during long-term storage relying on strain-specific characteristics cannot be excluded [ 41 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the same study, a positive effect of immobilization was also observed on the maintenance of cell viability during storage (for 180 days), which resulted in higher survival rates of the freeze-dried immobilized cultures on natural carriers (zea flakes and pistachios) in comparison to the free cultures. Regarding storage, low temperatures are known to prolong cell survival and are thus strongly preferred [ 44 , 45 ], but the nature of the carrier should not be neglected, as it may affect the cell viability throughout the final products’ shelf life and survival [ 46 ]. Nevertheless, the possibility of the viability of probiotic cultures (either in free form or immobilized on food ingredients) during long-term storage relying on strain-specific characteristics cannot be excluded [ 41 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the physicochemical parameters, the texture was satisfactory in the cereal bar, in several parameters (LASTA et al, 2021) and in the mortadella there was no statistical difference, compared to the conventional one in terms of hardness, adhesiveness, gumminess and chewing capacity. The addition of 0.05% of OPN mucilage was efficient to replace a high-caloric emulsifier (8.944% of chicken skin with fat)…”
Section: Sato Et Al 2019 Pasta (Tagliatelle) With Ora-pro-nóbis Flourmentioning
confidence: 83%
“…The plant grows spontaneously in naturally occurring areas but can be easily propagated by cuttings (KINUPP, 2007), with low incidence of diseases and water demand and good productivity even in unfavorable weather conditions. Some researches (BARREIRA et al, 2021;BOTREL et al, 2020;ALMEIDA et al, 2014;LASTA et al, 2021;MACIEL et al, 2021;SATO et al, 2019;SILVEIRA et al, 2020) suggest that ora-pro-nóbis is nutritionally rich and can be used in food preparations to promote health benefits. However, studies on its technicalfunctional properties and use in food products are still scarce, and no scoping review has been identified that unifies these themes.…”
Section: Introductionmentioning
confidence: 99%
“…Due to high demand of snack bars by nonathletes, sales have been on the increase in many countries such as the US, UK, Germany and Brazil (Sharma et al, 2014;Carvalho and Conti-Silva, 2017;Dahri et al, 2017;Pinto et al, 2017). By 2025, it is expected that the cereal bar market globally will reach $16.9 billion (Lasta et al, 2021). This could be attributed to high level awareness about convenient, natural, nutritious and healthy food products.…”
Section: Introductionmentioning
confidence: 99%